Having the Foggiest Idea: A Gradual Account on Mental Images - Šekrst, Kristina (Journal of NeuroPhilosophy, 2022)
First described by Galton in 1880 and then remaining unnoticed for a century, recent investigations in neuroscience have shown that a condition called aphantasia appears in certain individuals, which causes them to be unable to experience visual mental imagery. Comparing aphantasia to hyperphantasia – i.e., photo-like memory – and considering the neurological basis of perceptual phenomena, we are revisiting Hume's division of perceptions into impressions and ideas. By showing different vivacities of mental phenomena and comparing them to neurological research, we are stating that not only impressions and ideas differ "in the degrees of force and liveliness", but ideas and impressions amongst themselves as well. Such a gradual range of perceptions and mental images bears significant consequences for not only representational theory and historical interpretations but linguistics and semiotics as well.